Economic Digitalization for Consumers Legal Protection: Sharia E-Commerce Transaction in the New Era - Fina Olifia; Cici Sundari; Pidayan Sasnifa; Illy Yanti; Ilham Abdi Prawira (Faculty of Law, Universitas Pekalongan, 2024)
This study aims to analyze Legal Protection for Consumers in Sharia E-Commerce Transactions in the Era of Economic Digitalization. The research explores issues related to consumer legal protection within Sharia-based e-commerce transactions amidst the digital economic transformation. This study employs a qualitative research method with an exploratory approach. The researcher utilizes secondary data from online media, social media, and relevant journals by examining materials related to consumer legal protection in Sharia e-commerce transactions in the era of digitalization. The data analysis technique employs the NVivo 12 Plus software, a computer-assisted qualitative document analysis tool. This user-friendly software can process words, exploring word frequency, attributes, and cases derived from large datasets. Research findings indicate that Sharia e-commerce has significant potential to grow in Indonesia. The realization of this potential largely depends on the ability to address existing consumer protection issues. If the recommendations of this study are implemented, a safe and fair digital transaction environment, fully aligned with Islamic values and principles, can be established. Despite its rapid growth, Sharia e-commerce still requires substantial improvements to ensure consumer protection. To create a secure, just, and Sharia-compliant transaction environment, a holistic approach supported by the collective commitment of stakeholders is necessary. The ability to periodically address literacy, regulation, and technology issues, conduct regular audits, apply blockchain and AI for halal certification, and detect non-Sharia practices are key factors for success. The government, industry, and academia must collaborate to build an ideal ecosystem.